On Three-Point Boundary Value Problem - Sveikate, Nadezhda (Mathematical Modelling and Analysis, 2016)
Three-point boundary value problems for the second order nonlinear ordinary differential equations are considered. Existence of solutions are established by using the quasilinearization approach. As an application, the Emden-Fowler type problems with nonresonant and resonant linear parts are considered to demonstrate our results.